Respostas

A melhor resposta!
2014-09-03T21:44:02-03:00
Cara Não lembro se é assim que faz

4’ -30-2’+16=0                                    9’-4.3’+3=0
4’-2’-30+16=0                                     9’-12’=-3
2’-14=0                                              -3’=-3(-1)
2’=14                                                 3’=3
X=14/2                                               X=3/3
X=7                                                    X=1
3 5 3
obrigado!!!
só =D mais como eu falei não lembro se é assim que faz